P293 Insights from patients with Ulcerative Colitis on disease burden: Findings from a real-world survey in Europe. (21st January 2022) - Burisch PhD, J; Hart, A; Oortwijn, A; Khalid, J M; Hennessy, F; Knight, H; Meadows, R; Patel, H; Armuzzi, A
Abstract: Background: Ulcerative colitis (UC) requires life-long management with symptom control and disease remission being the ultimate goals. Despite existing treatments (Tx), there are patients without fully controlled disease which impacts their health-related quality of life (HRQoL). We investigated the disease burden, including residual disease symptoms and quality of life impairment, among moderate-severe UC patients in remission and not in remission. Methods: Data were drawn from Adelphi Inflammatory Bowel Disease (IBD) Disease Specific Programme, a point-in-time survey of gastroenterologists (GIs) and patients conducted in France, Germany, Italy, Spain and UK in Oct 2020-Mar 2021. Patient demographics, clinical characteristics (including mMayo components: stool frequency, rectal bleeding, endoscopic findings) and Tx history were reported by GIs while the patients reported symptoms, satisfaction with Tx, Short IBD questionnaire (SIBDQ), and EQ-5D at the time of consultation. Derived mMayo was used to define remission groups. Propensity score matching was used to compare outcomes among those with and without remission. Results: Data for 502 UC patients were included (mean age 38.9 years, 46% males, 67% employed, mean disease duration 5.2 years, and 61% treated with advanced therapies). At time of consultation, 74% of patients reported presence of symptoms, most frequent being fatigue (27%), abdominal pain (26%) and bowel movement urgency (26%); they were also reported as most bothersome symptoms (25%, 23%, 31% respectively) alongside bloody diarrhoea (28%). Since Tx initiation, patients stated no improvement in sexual problems (54%), sleep disturbance (47%), fatigue (33%), night-time urgency (27%) and no steroid reduction (22%). 37% of the patients were dissatisfied or believed a better control was possible with their Tx; common reasons were overall lack of efficacy (30%) and uncontrolled symptoms (30%). Symptoms reported by patients satisfied with their Tx vs those dissatisfied or believed a better control was possible are reported in Fig 1. Out of 502 patients, 66% (n=332) were in remission and yet reported that symptoms such as urgency, pain and fatigue remained (Fig 2). Whilst patients in remission had significantly better HRQoL measured by SIBDQ and EQ-5D, their scores were not optimal (Fig. 3, Fig. 4). Conclusion: We found that 66% of the UC patients have achieved remission, however 65% of those patients still reported residual symptoms. Quality of life aspects related to pain, discomfort, anxiety and depression still remained unaddressed among patients in remission. Our data highlights the need for a holistic approach to remission in the management of UC.